Expression of the nuclear gene encoding oxygen-evolving enhancer protein 2 is required for high levels of photosynthetic oxygen evolution in Chlamydomonas reinhardtii. - Mayfield, S P (1987)
We have cloned a cDNA encoding a 20-kDa polypeptide, oxygen-evolving enhancer protein 2 (OEE2), in Chlamydomonas reinhardtii. This polypeptide has been implicated in photosynthetic oxygen evolution, and it is associated with the photosystem II complex, the site of oxygen evolution in all higher plants and algae. The sequence of OEE2 cDNA, the deduced amino acid sequence of the preprotein, the N-terminal protein sequence of mature OEE2 protein, and the coding regions of the single OEE2 gene are presented. The protein is synthesized with a 57-amino acid N-terminal transit peptide that directs the transport of this polypeptide across three cellular membranes. A nuclear mutant of C. reinhardtii, deficient in oxygen-evolving activity, is shown to be specifically missing OEE2 polypeptides. This mutation, which results in the complete absence of all OEE2 mRNA and protein, does not affect the accumulation of other photosystem II polypeptides or their mRNAs.